Journal of Mathematical Imaging and Vision - Weickert, Joachim; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The Journal of Mathematical Imaging and Vision is a technical journal publishing important new developments in mathematical imaging. The journal publishes research articles, invited papers, and expository articles. Current developments in new image processing hardware, the advent of multisensor data fusion, and rapid advances in vision research have led to an explosive growth in the interdisciplinary field of imaging science. This growth has resulted in the development of highly sophisticated mathematical models and theories. The journal emphasizes the role of mathematics as a rigorous basis for imaging science. This provides a sound alternative to present journals in this area. Contributions are judged on the basis of mathematical content. Articles may be physically speculative but need to be mathematically sound. Emphasis is placed on innovative or established mathematical techniques applied to vision and imaging problems in a novel way, as well as new developments and problems in mathematics arising from these applications. The scope of the journal includes: computational models of vision; imaging algebra and mathematical morphology mathematical methods in reconstruction, compactification, and coding filter theory probabilistic, statistical, geometric, topological, and fractal techniques and models in imaging science inverse optics wave theory. Specific application areas of interest include, but are not limited to: all aspects of image formation and representation medical, biological, industrial, geophysical, astronomical and military imaging image analysis and image understanding parallel and distributed computing computer vision architecture design. The journal emphasizes its commitment to present coverage in these areas which span the interest of a global audience. The Editorial Board publishes manuscripts that are well-written and make a significant technical contribution.
Keywords: Image processing; Applied mathematics; Engineering mathematics; Physics; Signal processing; Speech processing systems; Image Processing and Computer Vision; Applications of Mathematics; Signal,Image and Speech Processing; Mathematical Methods in Physics